Review Artikel: Metode Teknologi Dalam Sistem Penghantaran Obat Transdermal Sediaan Patch - Assyfa; Azizah Nurhabibah; Nurul Maulida; Shofia Difa Aulia; Siti Nurcahyati; Yuliani Dewi; Nia Yuniarsih (Poltekkes Kemenkes Medan, 2022)
Transdermal is a route of drug administration through the skin, where many lipid layers are difficult to penetrate so that transdermal preparations are needed as a place for drug entry, for example creams and gels. The mechanism of drug delivery is through diffusion of the stratum corneum layer through lipid molecules, before releasing the drug in a controlled and constant manner followed by various other benefits and aims to increase the pharmacological effect in order to reach the maximum level. However, the permeability of the drug is not strong enough to pass through the stratum corneum. So we need a transdermal preparation that can work optimally and overcome the obstacles. This study aims to demonstrate the form, evaluation, formulation, and application of transdermal preparations in new drug delivery systems. Method used literature review of the 10 most journal articles and contains related information. Based on the research results, transdermal dosage forms differ depending on the level of concentration and each technological method needs adapted to the characteristics drug and the route of drug delivery given.